PERAN RUMAH PEMBIAYAAN PERTANIAN KSM JAYA AMANAH DALAM MENGIMPLEMENTASIKAN INKLUSI KEUANGAN PETANI - Selvi Jubaya; Eliana Wulandari (Universitas Galuh Ciamis, 2020)
The level of financial access in Indonesia is relatively low because of some obstacles that are faced by farmers in Indonesia to access formal financial institutions. KSM Jaya Amanah is one of the institutions that seeks to implement the financial inclusion of farmers through an empowerment program i.e the agricultural financing house. This research aims to identify the role of KSM Jaya Amanah in implementing financial inclusion in Pacet Subdistrict, Bandung District. Data analytical methods used in this research is descriptive statistics. The results of the analysis showed that several efforts have been made by KSM Jaya Amanah in implementing financial inclusion for farmers through the agricultural financing house program that focuses to provide financial access for farmers who are considered unbankable people. The agricultural financing house has a positive impact on the farm results of its members. The barriers faced by the KSM in implementing financial inclusion include lack of funds from investors and lack of the management resources.